INSTITUTIONAL PROVISION OF SOCIAL PARTNERSHIP IN PUBLIC ADMINISTRATION - Samoilenko A.P. (Pressing Problems of Public Administration, 2018)
The regulatory factors in ensuring the formation of partnership relations in the state are investigated. The institutional basis for the functioning of social partnership process and the main problems of its formation and development are analyzed. The role of partnership relations in the process of social partnership under modern conditions has been clarified.